Athena in the Classical World - Deacy, Susan,; Villing, Alexandra, (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
Among ancient Greek deities, none has enjoyed as rich a life as Athena - goddess of war, wisdom and the arts - and she continues to fascinate and challenge today. This volume sheds light on the goddess more comprehensively than has previously been attempted. It brings together the latest research, centring on Greek and Roman religion, literature and archaeology, yet also encompassing ancient Near Eastern, Indo-European, and modern interpretations. Cults and myths are explored, as are political, social, and gendered roles, and art historical and etymological developments. Recurrent themes are investigated, as are the many dividing lines and contradictory aspects which characterise representations of the goddess. The volume will enhance our understanding of Athena, and will be a source of inspiration for new ideas and interpretations for years to come.